Animals Property & The Law - Francione, Gary L. (Gary Lawrence), 1954- (Book collections on Project MUSE., 1995)
""Pain is pain, irrespective of the race, sex, or species of the victim," states William M. Kunstler in the Foreword. This moral concern for the suffering of animals and their legal status is the basis for Gary L. Francione's profound book, which asks, Why has the law failed to protect animals from exploitation?" "Exploring every facet of this heated issue, Francione discusses the history of the treatment of animals, anticruelty statutes, vivisection, the Federal Animal Welfare Act, and specific cases such as the controversial injury of unanesthetized baboons at the University of Pennsylvania. He thoroughly documents the paradoxical gap between our professed concern with humane treatment of animals and the overriding practice of abuse permitted by the law."--Jacket